'Time Capsule' Archiving through Strong Dark Archives (SDA): Designing Trustable Distributed Archives for Sensitive Materials. Issue 3 (2nd October 2021) - Bowers, John; Cushman, Jack; Sarathy, Jayshree; Zittrain, Jonathan
ABSTRACT: Archivists regularly contend with a wide range of security threats, including data breaches, inadvertent loss, and legal action by those hoping to make sealed records public. These threats are particularly salient when sensitive materials are donated with delayed-release conditions. Trust in archivists' ability to enforce such conditions gives donors the confidence to enter into the historical record materials that they might otherwise destroy. But as these materials are increasingly born-digital (and therefore hackable, convenient to exfiltrate en masse, and more easily corrupted), and as governments and private parties become ever more aggressive in their efforts to secure early releases, we must innovate in order to stand still. To compensate for these new dynamics, we propose Strong Dark Archives (SDA), a blended legal and technical protocol for securing delayed-released archival materials among a network of libraries. SDA leverages modern cryptography and institutional agreements to coordinate access-control across multiple accredited archival organizations, providing broad resilience to data breaches, technical failures, and legal process. Through this distributed approach to security, SDA imposes meaningful friction on efforts to force the early disclosure of archival records.